Trends in antiretroviral use in pregnancy in the UK and Ireland, 2008–2018. Issue 4 (18th February 2022) - Rasi, Virginia; Peters, Helen; Sconza, Rebecca; Francis, Kate; Bukasa, Laurette; Thorne, Claire; Cortina‐Borja, Mario
Abstract: Introduction: HIV treatment recommendations have evolved over time, reflecting both growing availability of new antiretrovirals and accumulating evidence on their safe and effective use. We analysed patterns of antiretroviral use among diagnosed pregnant women living with HIV delivering in the UK and Ireland between 2008 and 2018 using national surveillance data. Methods: All singleton pregnancies with known outcomes and known timing of antiretroviral initiation reported to the National Surveillance of HIV in Pregnancy and Childhood were included. Every individual instance of specific antiretroviral use was the unit of analysis in generating a snapshot of antiretroviral use overall and over calendar time. The final analysis was restricted to the 14 most frequently prescribed antiretrovirals. Results: There were 12 099 singleton pregnancies reported during 2008–2018 and a total of 38 214 individual uses of the 14 most commonly prescribed antiretrovirals, the majority of which were started before conception (70.9%). In 2008, 37.7% (482/1279) of pregnancies were conceived under treatment, reaching 80.9% (509/629) by 2018. Patterns of antiretroviral use have changed over time, particularly for third agents. Between 2008 and 2018 the most frequently used protease inhibitor shifted from lopinavir to darunavir, whereas use of integrase inhibitors increased steadily over time. Conclusions: These national surveillance data enable investigation of the 'real‐world' use of antiretrovirals in pregnancy on a population level. Findings demonstrate mixed responsiveness of antiretroviral prescription to changes in pregnancy guideline recommendations and may also reflect changes in commissioning and in the characteristics of pregnant women living with HIV.